Economic Reforms and Cost Efficiency in the Banking Sector in India - Khurana, Ajay; Khosla, Rajiv (Indian Journal of Finance, 2019)
This research paper sought to examine the level and extent of cost efficiency and its correlates pertaining to 51 sample banks operating in India during the post-reform period (1995-2016). Results pointed toward the existence of significant variations across banks in respect of their cost efficiency scores that ranged between 66.94% and 99.49% during 1995-2016, with a mean efficiency score at 0.7960. It signified that on an average, each sample bank, if it were producing on the frontier rather than at its current location, could have done so by using only 79.6% of the resources actually employed by it. Conversely speaking, it also means that it was found involved in expending 20.40% additional resources and thus, incurred higher cost to produce the same level of output as the average efficient bank. Moreover, it was also observed that as a source of cost inefficiency within all inefficient banks, allocative inefficiency weighed slightly more than its technical inefficiency counterpart and important factors like ownership, NPAs, and expansion affected cost efficiency and their correlates of commercials banks in India.